Cases in adversiting and promotion management - Quelch, John A.; Farris, Paul W. (Boston, EE.UU : Irwin, 1991)
PART 1. Adversiting, promotion and marketing communications ; PART 2. Adversiting, branding, and positioning ; PART 3. Message strategy and copy testing ; PART 4. madia strategy ; PART 5. Budgeting ; PART 6. Sales promotion: strategy and tactics, PART 7. Point-of-Purchase Merchandising ; PART 8. Agency Relations and Management ; PART 9 Social and Ethical Issues ; PART 10. Projects and exercises in Advertising and Promotion Management.
1. Adevertising, romotion, and marketing communications. -- 2. Advertising, branding, and positionong. -- 3. Message strategy and copy testing. -- 4. Media strategy. -- 5. Bodgeting. -- Sales promotion: strategy and tactics. -- Point-of-Purchase Mercandising. -- 8. Agengy Relations and Management. -- 9. Social and Ethical Issues. -- 10. Projects and exercises in Advertising and Promotion Management
Incluye bibliografía e índice
Keywords: PUBLICIDAD -- ADMINISTRACION; PROMOCION DE VENTAS